2018
DOI: 10.3329/bjmb.v10i1.36694
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin and Plasma Fibrinogen Level in Acute Ischemic Stroke

Abstract: Acute ischemic stroke is the primary pathology of brain vascular system that temporarily or permanently affects brain functions as a result of ischemia. In ischemic stroke events, many biochemical and immunological reactions occur secondarily in response to the reduced cerebral blood flow. Brain tissue damage after acute ischemic stroke is mediated partly by inflammation induced by ischemia-reperfusion injury. It is thought that acute ischemic stroke due to cerebral ischemia triggers acute phase reaction and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Similar studies were performed by Mandal et al, Koul et al, Mehrpour and Meharpour conducted a prospective cohort study that concluded that the level of serum ferritin is greater than 164.1ng/ml in the first 24 hours after admission is a reasonably important predictor for hemorrhagic transformation of ischemic stroke. 11,12 Pandey et al studied the thyroid dysfunction in patients of ischemic cerebrovascular accidents and concluded the relationship between low values of FT3, FT4, and low scores on S.S.S. and G.C.S.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were performed by Mandal et al, Koul et al, Mehrpour and Meharpour conducted a prospective cohort study that concluded that the level of serum ferritin is greater than 164.1ng/ml in the first 24 hours after admission is a reasonably important predictor for hemorrhagic transformation of ischemic stroke. 11,12 Pandey et al studied the thyroid dysfunction in patients of ischemic cerebrovascular accidents and concluded the relationship between low values of FT3, FT4, and low scores on S.S.S. and G.C.S.…”
Section: Discussionmentioning
confidence: 99%